Using local ecological knowledge to access the distribution of the Endangered Caatinga howler monkey (Alouatta ululata) - Freire Filho, Roberio Gomes; Pinto, Thieres; Bezerra, Bruna Martins (Ethnobiology and Conservation, 2018)
Traditional or Local Ecological Knowledge (LEK) has contributed to the development of conservation strategies for many species, including primates. A lack of basic knowledge about the Endangered Caatinga howler monkey (Alouatta ululata) in Northeastern Brazil makes it difficult to design and implement effective conservation strategies. We aimed to improve our understanding of the geographic range of A. ululata, collect LEK on the species, and understand how people interact with these howlers. We conducted semi-structured interviews with members of local communities in two regions within the currently known distribution range of the Caatinga howler monkey. The maps were constructed based on the information currently available in the literature and on the data obtained through our semi-structured interviews. We identified new areas of occurrence for Caatinga howler monkeys, increasing the species’ range in a Northeastern direction in the state of Ceará. Gross domestic product (GDP) and population size were inversely related to the amount of knowledge that the local human population showed about the Caatinga howler monkeys. Local knowledge of howling hours and seasons may increase the chances of researchers locating the species, optimizing time and funding resources. Despite a positive attitude towards Caatinga howler monkeys in both regions (i.e. howlers were not killed in retaliation for crop raiding and locals found their vocalizations pleasant), we identified poaching and medicinal uses of the species. Our data demonstrated that the range of Caatinga howler monkeys was larger than previously recorded and also that local knowledge was crucial for triangulating the species location.